Proceedings of the Padang International Conference on Educational Management and Administration (PICEMA 2018) 2019
DOI: 10.2991/picema-18.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the School Principals Candidates Training Program in LPMP of West Nusa Tenggara Province

Abstract: The research is aimed to evaluate the training program candidates of school principals in LPMP West Nusa Tenggara Province. This research uses qualitative approach, evaluative research method with Robert Stake Responsive Evaluation Model. Data collection techniques uses observation, interviews, and documentation studies. The results of the study of training program explain: (1) Antecedent of training program, in general have met the evaluation criteria. As for the aspect of facilities, especially the classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In other words, the impact of school principal strengthening training on school principal performance is still unclear. So, this study supports the finding that school heads management style has a moderate impact on school performance [6]. Meanwhile, principals with high performance are relatively balanced with principals who are low performing.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In other words, the impact of school principal strengthening training on school principal performance is still unclear. So, this study supports the finding that school heads management style has a moderate impact on school performance [6]. Meanwhile, principals with high performance are relatively balanced with principals who are low performing.…”
Section: Resultssupporting
confidence: 86%
“…By participating in PPKS, it is expected that there will be an increase in the competence of school principals who are able to think visionary in leading and managing their schools so that management and quality culture can be realized in highly competitive schools [5]. However, a study found a training program for prospective school principals was running effective and efficient [6] but did not reach the effect of the training on the performance of school principals in their workplace. For this reason, this study seeks to examine whether school principal strengthening training can improve the performance of school principals?…”
Section: Introductionmentioning
confidence: 99%
“…General training objectives describe the objectives to be achieved at the end of the training. The specific objectives of the training describe more specifically, the objectives to be achieved in order to achieve the general objectives of the training (Irawan et al, 2018). The purpose of the training conducted in our SMART-based research is to improve the competence of guidance and counselling teachers with the specific aim of providing one-on-one skills training.…”
Section: Planning On Smartmentioning
confidence: 99%
“…The development of a SMART-based training management model is carried out using field trials and internal testing by experts through focus group discussions (FGD). FGD is a method of exploring the special phenomenon of group discussion that focuses on joint activities among the individuals involved in it to produce a mutual agreement (Irawan et al, 2018;Lehoux et al, 2006). The feasibility of the model developed in this study was tested internally through FGD, attended by 18 users, 6 practitioners and 5 experts.…”
Section: Feasibility Of the Guidance And Counselling Special Service ...mentioning
confidence: 99%